Increased plasma levels of IL-6 are associated with striatal structural atrophy in major depressive disorder patients with anhedonia - Lu, Shaojia; Wu, Congchong; Jia, Lili; Fang, Zhe; Lu, Jing; Mou, Tingting; Hu, Shaohua; He, Hongjian; Huang, Manli; Xu, Yi (Frontiers in Psychiatry, 2022)
Background Anhedonia, as the core endophenotype of major depressive disorder (MDD), is closely related to poor prognosis, but the mechanism of this feature remains to be understood. The aim of this study was to investigate the inflammatory factors and brain structural alterations in MDD patients with anhedonia and evaluate the relationship between these factors. Methods We assessed the plasma levels of interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) in MDD patients with anhedonia (n = 22), MDD patients without anhedonia (n = 20), and age- and sex-matched healthy controls (HCs, n = 20) by enzyme-linked immunosorbent assay kits. All participants underwent high-resolution brain magnetic resonance imaging (MRI) scans, and voxel-based morphometry (VBM) was used to evaluate their gray matter volume (GMV). We compared inflammatory factors and GMV among the three groups and explored their relationships in MDD patients with anhedonia. Results Compared with those of HCs, plasma levels of IL-1β were increased in patients with MDD independent of anhedonia features, while plasma levels of IL-6 were elevated in MDD patients with anhedonia only. Meanwhile, MDD patients with anhedonia exhibited reduced GMV in the left striatal structures compared to MDD patients without anhedonia and HCs. Moreover, a significant association was observed between increased plasma levels of IL-6 and decreased GMV of the left putamen in MDD patients with anhedonia. Conclusions The present research outcomes suggest that anhedonia is associated with increased plasma levels of IL-6 and decreased GMV in the left striatal structures. In addition, this study demonstrates that GMV loss in the left putamen is related to increased plasma levels of IL-6 in MDD with anhedonia, which provides further insights into the possible mechanisms of anhedonia.